Reform in Translation: The Swedish Transport Administration’s Quest for a New Mission Statement - Rämö, Hans; Wittbom, Eva (Scandinavian Journal of Public Administration, 2022)
The long-term outcomes of reform processes in the public sector remain understudied in the literature. This study investigates the Swedish Transport Administration (STA) employees’ and managers’ translation and internalization of their new role as societal developers. Since the STA’s founding in 2010 and until 2018, the STA head office neither guided nor centrally determined how to define and understand the STA’s role as a societal developer. We examine this internalization process through the lens of Czarniawska’s translation model of the distribution of ideas as a collective creation through local translation and adaptation. The study shows that the ongoing friction that occurs when the concept and role of a societal developer are discussed and disseminated within an organization is influenced by prevailing identities and local action nets. It also shows that the translation of this new role eventually failed, due to either it being submerged within already-existing concepts or it having a perceived lack of relevance. We conducted this mixed-method study over six years (2016–2021) using documentary analysis, workshop participation, interviews and a survey.